Improved colour stability of phosphorescent white organic light-emitting devices by manipulating electron transport. Issue 1 (16th June 2014) - Wang, Xu; Zhao, Juan; Zhong, Jian; Yu, Junsheng
Abstract : Phosphorescent white organic light-emitting devices (WOLEDs) with a multilayer structure were fabricated, and colour stability was studied by manipulating electron transport property of the hole-blocking layer 1, 3, 5-tris(2-N-phenylbenzimidazolyl)benzene (TPBi) and the electron transporting layer 4, 7-diphenyl-1, 10-phenanthroline (Bphen). With 20 nm thick TPBi and 20 nm Bphen tailoring electron transport, the WOLED yielded a slight Commission Internationale de l'Eclairage coordinates variation of (−0.003, 0.007) in a wide range of bias voltages. Additionally, a peak current efficiency of 32.4 cd/A and a peak external quantum efficiency of 12.7% were also realised. It was found that the enhancement of colour stability was due to optimisation of the electron transport, by adjusting the thicknesses of TPBi and Bphen to improve the charge carrier balance.